2016
DOI: 10.1038/srep18460
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intent Modulates The Neural Substrates Of Creativity: An fMRI Study of Emotionally Targeted Improvisation in Jazz Musicians

Abstract: Emotion is a primary motivator for creative behaviors, yet the interaction between the neural systems involved in creativity and those involved in emotion has not been studied. In the current study, we addressed this gap by using fMRI to examine piano improvisation in response to emotional cues. We showed twelve professional jazz pianists photographs of an actress representing a positive, negative or ambiguous emotion. Using a non-ferromagnetic thirty-five key keyboard, the pianists improvised music that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 45 publications
(58 reference statements)
3
44
0
Order By: Relevance
“…It is thought that increased activity in the MFC may denote internally directed attention involved with creativity tasks as well as coordination of complex action underlying sequential planning that is an integral part of improvisation of music (Dolan et al, 2013;Beaty, 2015;Dikaya and Skirtach, 2015;Landau and Limb, 2017;Stevens and Zabelina, 2019). Our finding of greater power for improv over scale in the frontal area comprising regions of the MFC, ACC, and SMA (Figure 2, Table 1) are consistent with many fMRI studies investigating improvisation (Bengtsson et al, 2007;de Manzano and Ullén, 2012a,b;Donnay et al, 2014;Pinho et al, 2014;McPherson et al, 2016;Landau and Limb, 2017;Lu et al, 2017;Dhakal et al, 2019). The low alpha range has been implicated with general attentional demands and the upper alpha band to task-specific demands often related to creativity (Fink and Benedek, 2014).…”
Section: Brain Related Activity Differentiating Improv and Scalesupporting
confidence: 85%
“…It is thought that increased activity in the MFC may denote internally directed attention involved with creativity tasks as well as coordination of complex action underlying sequential planning that is an integral part of improvisation of music (Dolan et al, 2013;Beaty, 2015;Dikaya and Skirtach, 2015;Landau and Limb, 2017;Stevens and Zabelina, 2019). Our finding of greater power for improv over scale in the frontal area comprising regions of the MFC, ACC, and SMA (Figure 2, Table 1) are consistent with many fMRI studies investigating improvisation (Bengtsson et al, 2007;de Manzano and Ullén, 2012a,b;Donnay et al, 2014;Pinho et al, 2014;McPherson et al, 2016;Landau and Limb, 2017;Lu et al, 2017;Dhakal et al, 2019). The low alpha range has been implicated with general attentional demands and the upper alpha band to task-specific demands often related to creativity (Fink and Benedek, 2014).…”
Section: Brain Related Activity Differentiating Improv and Scalesupporting
confidence: 85%
“…The authors theorised that low‐creative individuals rely on procedural memory rather than generating completely novel material; however, how these connections change with instrumental improvisation, a necessarily procedural memory‐driven behaviour, is a relevant avenue for future research. Hippocampus involvement in improvisation was described by McPherson, Barrett, Lopez‐Gonzalez, Jiradejvong, and Limb () who found that emotionally cued improvisation for positive, ambiguous and negative emotions was related to deactivation in the left, right and bilateral hippocampus, respectively. Whether these deactivations are part of a general improvisation network or specifically related to emotional tasks is unclear.…”
Section: Top‐down Networkmentioning
confidence: 86%
“…Since participants in the current study included participants who were musicians but not necessarily pianists and not advanced improvisers, it is likely that our task mirrored more closely the ambiguous condition in McPherson et al (2016). In other words, since the majority of the current participants were not pianists, the necessary movements were not overlearned and therefore required more engagement by the SMA.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in the current task, the SMA is probably involved in continuous monitoring of current and planned motor movements. Interestingly, new research suggests this monitoring function of the SMA is stronger during spontaneous creation of a musically ambiguous emotional output, while a highly practiced overlearned output requires less monitoring (McPherson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%